Effects of partial root drying, regulated deficit irrigation and mycorrhiza on growth performance and physiological responses of rock melon (Cucumis melo L.) - Mohd Noor, Hamdan (2015)
Rock melon (Cucumis melo L.), one of the most popular and delicious fruits of Malaysia has great potential for commercial development. Currently, rock melon is most widely cultivated under rain shelter structure using soilless culture. In principle,the partial root drying (PRD) or regulated deficit irrigation (RDI) technique has been used to evaluate the biochemical responses of water deficit without actually disturbing the physiological effects of plant growth under reduced water availability. This study aimed to determine the effects of deficit fertigation on both vegetative and reproductive growth of melon. Two fertigation techniques were used namely: 1) Partial root drying (PRD) and 2) Regulated deficit irrigation (RDI). The experiment comprise the following treatments: 1) Well watered (WW) - watered manually at 100 % SC (substrate capacity); 2) (RDI) at 50 % SC and 3) (PRD) at 50 % SC, split into two compartments alternating wet and dry period once every 2 days. Different deficit irrigation levels had significant effects on dry matter production and yield of melon as compared to controls. Maximum and significant yield of melon was from the WW and RDI plants. Moderate water stress (RDI) did not drastically reduce fresh fruit weight of melon (511.11 g compared to WW with 710.74 g), i.e. only 28 % drop in yield,indicating better utilisation of the available water. Under the PRD treatment, yield was only 144.11 g plant-1 i.e. an 80 % drop in yield. Maximum total soluble solids (TSS) of 14.02 oBrix was from WW treated plants as compared to 13.83 oBrix of RDI and 5.99 oBrix of PRD plants respectively. Total proline concentration in leaf at 76 DAT clearly illustrates that the PRD plants is highly stressed by this deficit system with maximum reading of 21.44 μg g-1 as compared to only 9.68 and 9.96 μg g-1 from WW and RDI plants respectively. In general, plants that experiencing serious water stress tend to produce higher proline concentration. The RDI technique for melon production in soilless culture is recommended for the subsequent experiment with arbuscular mycorrhiza (AM) fungi. Presence of the AM fungi in combination with RDI (RDI+M treatment), significantly enhanced plant growth, dry matter production and yield of melon. At 76 DAT, results obtained from RDI+M plants gave almost similar results to the WW plants for almost all parameters measured. The WW and RDI+M plants produce respectively higher (930 g and 950 g plant-1) and quality fruits, with high Brix Index of 15.05 o and 15.26 oBrix respectively. Non mycorrhizal plants (RDI-M) only produced smaller sized fruit of 670 g plant-1 and Brix Index of 14.15 oBrix. Cucumis melo plants showed high dependance 178.53 % on AM fungi, with root colonisation of 97.5 %. The introduced AM inoculum also sporulate abundontly with, ± > 200 spores /100 g media used at both harvests (31 DAT and 76 DAT), i.e. 191.75 and 222.50 respectively.